Dekadensi Spiritual Remaja Katolik Akibat Konsumsi Minuman Keras Dalam Telaah Partisipasi Menggereja di Lingkungan Santo Kristoforus Kampung Baru - Sarang, Rikardus Kristian; Oywatorop, Benedikta (Jurnal Masalah Pastoral, 2024)
This study aims to identify and analyze the impact of alcohol consumption on the spiritual decadence of Catholic teenagers, particularly in relation to their participation in church life in the Santo Kristoforus Kampung Baru Neighborhood. Using a qualitative-descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation of fifteen purposively selected teenagers. The results showed that alcohol consumption is a significant factor that disrupts the spiritual life of teenagers. This phenomenon is reflected in a decrease in the frequency of attendance in worship, minimal involvement in ecclesiastical activities, and weak interpretation of the teachings of the Catholic faith. In addition, there are also supporting factors such as lack of parental supervision, weak pastoral care, and negative influences from the social environment. This study recommends strengthening the Church's youth mentoring program, increasing the role of the family in faith education, and collaboration across pastoral sectors in restoring the spirituality of decadent adolescents.